The Impact of Enterprise Resource Planning on Operational Performance through Supply Chain Orientation in Faradaneh Company - Abbas Ghaedamini Harouni; Meysam Babaeefarsani; Mehrdad Sadeghi De Cheshmeh; Gholam Reza Maleki Farsani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The main objective of this study is to investigate the impact of Enterprise Resource Planning (ERP) on Operational Performance (OP) through Supply Chain Orientation (SCO) in Faradaneh company.Methodology: The present study is a descriptive survey regarding research methods. A standard questionnaire by Acar et al. [1] was used to measure the variables of the research model. The questionnaire was implemented through the participation of 135 managers and employees of Faradana company who were selected by stratified random sampling after measurement of validity (face and content validity based on Lawshe's method, confirmatory and exploratory factor analysis, convergence, and divergence) and reliability (Cranach's alpha method and hybrid).Findings: The results showed that ERP had a significant and strong effect on the OP of Faradaneh company by mediating the SCO, indicating the high predictive power of the ERP components (With a coefficient of determination of 0.93). Also, the ERP Pathway had the most effect on OP, with a path coefficient of 0.71 and a significance of p < 0.001. The value of the present study is due to content innovation (simultaneous use of ERP variables, OP, and SCO) and method (using different validity and reliability methods).Originality/Value: The present study investigates the effect of organizational resource planning on OP through SCO on the Faradaneh Aquatic Food Production Company employees.